Pericecal fossa strangulated internal hernia. Issue 4 (10th February 2021) - Seretis, Charalampos; Katz, Christian; Ahmed, Aftab; Palit, Amitabh; Piramanayagam, Balasubramaniam; Marimuthu, Kalimuthu
Abstract: Pericecal fossa internal hernias are a rare cause of intestinal obstruction, and high clinical suspicion is required to diagnose them. Abstract : Pericecal fossa internal hernias are a rare cause of intestinal obstruction, and high clinical suspicion is required to diagnose them.